MicroRNA‐448 overexpression inhibits fibroblast proliferation and collagen synthesis and promotes cell apoptosis via targeting ABCC3 through the JNK signaling pathway. Issue 2 (10th September 2019) - Xu, Feihong; Xu, Fei; Xie, Shiguang; Zuo, Wei; Wen, Guilan; Zhao, Tiantian; Wan, Xuan
Abstract: Idiopathic pulmonary fibrosis (IPF) is a condition that results in the progressive deterioration of lung function with poor prognosis. The current study is aimed at exploring how microRNA‐448 (miR‐448) targeting ABCC3 affects fibroblast proliferation, apoptosis, and collagen synthesis of mice with IPF via the Jun N‐terminal kinase (JNK) signaling pathway. Bioinformatics and dual‐luciferase polymerase chain reaction were used to predict the relationship of miR‐448 and ABCC3. The expression of miR‐448 and ABCC3 was detected in IPF tissues. Using IPF mouse models, lung fibroblasts for the experiments were treated with miR‐448 mimic, miR‐448 inhibitor, si‐ABCC3, or SP600125 (inhibitor of JNK) to evaluate the cell proliferation and apoptosis in response to miR‐448. Reverse transcription quantitative polymerase chain reaction and western blot analysis were used to identify the expression of miR‐448, ABCC3, and the activation of the JNK signaling pathway. ABCC3 was targeted and downregulated by miR‐448 based on bioinformatics prediction and dual‐luciferase reporter gene assay. Additionally, miR‐448 was found to be highly expressed in IPF lung tissues with low expression levels of ABCC3. In response to the treatment of miR‐448 mimic or si‐ABCC3, lung fibroblasts exhibited decreased cell proliferation and increased apoptotic rates, whereas the miR‐448 inhibitor reversed the conditions. Notably, we also found that miR‐448 mimic inhibited the JNK signaling pathway. In conclusion, by using miR‐448 to target and downregulate ABCC3 to block the JNK signaling pathway in mice with IPF, we found an increase in fibroblast apoptosis, inhibited cell proliferation, and decreased collagen synthesis of fibroblasts. Abstract : MicroRNA‐448 (miR‐448) is lowly expressed yet ABCC3 is highly expressed in lung tissues of idiopathic pulmonary fibrosis (IPF) mice; ABCC3 is the target gene of miR‐488; miR‐448 overexpression promoted apoptosis of lung fibroblasts in IPF.